2005
DOI: 10.2139/ssrn.881547
|View full text |Cite
|
Sign up to set email alerts
|

Fifteen Years of Economic Reform in Russia: What Has Been Achieved? What Remains to Be Done?

Abstract: The paper provides an overview of the course of economic reform and the performance of the Russian economy since the early 1990s and an analysis of the structural reform challenges ahead. It assesses the contribution of institutional and structural reforms to economic performance over the period, before turning to the question of where further structural reforms could make the biggest contribution to improved performance. Three major conclusions emerge. First, there is still a great deal to be done to strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Among the first studies on the economic performance of Russian regions, Mikheeva (1999) and Popov (1999) resource endowments and industrial structure, explain the differences in regional growth, whereas only natural resources remain significant in periods of growth, when other factors such as political reforms contribute to the path. In previous papers (Ahrend 2005(Ahrend , 2006Ahrend and Tompson 2005), no evidence of convergence can be established controlling for initial industrial production, though convergence is found in real income. Guriev and Vakulenko (2012) perform inequality decompositions by income sources and study convergence in Gross Regional Product, incomes and wages.…”
Section: Related Literaturementioning
confidence: 88%
“…Among the first studies on the economic performance of Russian regions, Mikheeva (1999) and Popov (1999) resource endowments and industrial structure, explain the differences in regional growth, whereas only natural resources remain significant in periods of growth, when other factors such as political reforms contribute to the path. In previous papers (Ahrend 2005(Ahrend , 2006Ahrend and Tompson 2005), no evidence of convergence can be established controlling for initial industrial production, though convergence is found in real income. Guriev and Vakulenko (2012) perform inequality decompositions by income sources and study convergence in Gross Regional Product, incomes and wages.…”
Section: Related Literaturementioning
confidence: 88%
“…He identifies which factors affect economic growth during periods of crisis and growth: in the former scenario, initial conditions, in particular resource endowments and industrial structure, explain the differences in regional growth, whereas only natural resources remain significant in periods of growth, when other factors such as political reforms contribute to the path. In previous papers (Ahrend 2005(Ahrend , 2006Ahrend and Tompson 2005), no evidence of convergence can be established controlling for initial industrial production, though convergence is found in real income. Guriev and Vakulenko (2012) perform inequality decompositions by income sources and study convergence in Gross Regional Product, incomes and wages.…”
Section: Related Literaturementioning
confidence: 88%
“…Few countries have experienced more dramatic changes in their economic environment as did Russia in the last decade of the 20 th century, after the disintegration of the Soviet Union and during the transition from a centrally planned structure to a capitalist market economy, and trade policy was no exception. The reconstruction of the country's foreign trade structure, after 1991, was almost complete, starting from measures as fundamental as the abolition of the state monopoly in trade, the elimination of widespread quantitative controls, and the implementation of a tariff structure (Ahrend and Tompson, 2005).…”
Section: Historical Backgroundmentioning
confidence: 99%